The bounds of sense : an essay on Kant's Critique of pure reason - Strawson, P. F. (University paperbacks, 1975)
This influential study of Kant in which Strawson seeks to detach the true analytical and critical achievement of Kant's work from the unacceptable metaphysics with which it is entangled.